PENYELESAIAN SENGKETA PROSES PEMILIHAN KEPALA DAERAH DAN WAKIL KEPALA DAERAH KABUPATEN KENDAL TAHUN 2024 - Farras Narendra Fata; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2026)
This study was motivated by the occurrence of procedural disputes in the nomination stage of the 2024 Kendal Regency Head Election, which began with the return of candidate pairs' files by the Kendal Regency KPU and continued with the resolution of disputes through the adjudication mechanism at the Kendal Regency Bawaslu. This study aims to analyze the dynamics of the dispute resolution and examine the extent to which the resolution practice reflects the principles of the Electoral Justice System. This study uses a qualitative approach with a case study method, with data collection techniques through interviews and literature studies. Research informants included election organizers at the regional level, political party representatives, and parties involved in the dispute process. The results of the study show that the handling of disputes by the Kendal Regency Bawaslu tends to emphasize compliance with administrative procedures in accordance with the applicable regulatory framework, but has not fully realized substantive protection of electoral rights within the framework of Electoral Justice. In addition, the disputes that arose were not solely caused by administrative issues, but were also a manifestation of the political dynamics of candidacy, which were then mediated through regulatory instruments and technical mechanisms for organizing elections. The ambiguity of norms in the regulation of candidacy also opens up room for multiple interpretations that are exploited in the context of political contestation, thus implying limited space for candidacy in the 2024 Kendal Regency Election. Therefore, it is necessary to strengthen the orientation of Electoral Justice in a more substantive manner and improve the quality of candidate nomination regulations to make them clearer and more consistent in order to minimize similar disputes in the future.